Pengaruh Social Media Marketing, Viral Marketing dan Celebrity Endorser terhadap Keputusan Pembelian Produk Fashion RS31 Shop House pada E-Commerce Shopee - Rachmatika, Fera; Maslichah, Maslichah; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this study was to determine how social media marketing, viral marketing, and celebrity endorsers influence consumer decisions in buying RS31 Shop House fashion products at Shopee. Purposive sampling is the sampling technique used in this quantitative research. Thus, the sample of this study consisted of 85 respondents. Multiple linear regression analysis was used in this study. The results showed that social media marketing (X1), viral marketing (X2), and celebrity endorsers (X3) simultaneously had a positive and significant effect on purchasing decisions for RS31 fashion products from Shopee e-commerce. Partially, purchasing decisions are positively and significantly influenced by social media marketing (X1), viral marketing (X2), and celebrity endorsers (X3). Keywords: social media marketing, viral marketing, and celebrity endorsers